Kinetic Parameters Analysis of Liver and Kidney Catalase Under The Influence of Cadmium and Mercury In Vitro - Karantika, Ellsa Anggun; Supianur, Supianur; Edyson, Edyson; Suhartono, Eko (Journal of Tropical Life Science, 2016)
Cadmium (Cd) and mercury (Hg) are toxic metals that affect human organs function, including liver and kidney. This toxic activity is because the heavy metal could induce oxidative stress and interfere antioxidant activities, including catalase (CAT). The present study was aims to evaluate the effect of Cd and Hg to liver and kidney CAT kinetic parameters in vitro. In this experiment, liver and kidney were taken from male rats (Rattus novergicus). Sample the homogenized and divided into three groups with; T0 served as control which contains liver or kidney homogenate + H2O2, T1 which contains liver or kidney homogenate + H2O2 + 0.03 mg/L CdSO4; and T2 which contains liver or kidney homogenate + H2O2 + 1 mg/L Hg. Solutions then incubated at 37ÂºC for 1 hour and then was prepared for CAT activity measurement. The CAT activity was measured using spectrophotometer at 240 nm. For measuring the kinetic parameters, different concentration of H2O2 were used. The kinetics parameters (Km and Vmax) were calculated using Lineweaver-Burk plot. The results shows that Cd and Hg could decrease the affinity of CAT-H2O2 complex which expressed by the higher Km and Vmax values. Also from the results, Cd has better activity to decreased the affinity of CAT-H2O2 complex than Hg. From this results, it can be concluded that Cd and Hg treatments could inhibit CAT activity in liver and kidney in vitro.